Performance Audit on Rashtriya Madhyamik Shiksha Abhiyan in Mizoram (2013-2018) - CAG of India (CAG of India)
Planning process for identification of uncovered habitations for secondary schools and their coverage has not been done systematically. The number of eligible habitations that remained out of coverage of secondary education was 392 (46 per cent) as of end of 2017-18. Non-preparation of perspective and annual plans with local input from the schools has resulted in a situation where infrastructure was provided without immediate requirement and therefore, not utilised. State norms were not complied with while designing and constructing class rooms, computer labs, libraries, etc. Drinking water facilities were not provided in several new schools. Despite the emphasis on provision of ICT facilities by GoI, these were not developed/ provided. Same was the case with children with disabilities/ special needs, where the services of Special Educators were utilised elsewhere. While laboratory infrastructure was yet to be set up, Laboratory Assistants were prematurely posted to 58 schools. Efforts need to be made to bring about equity in secondary education, as most of the uncovered habitations continue to be in the rural and remote areas.
For the Period 2015-2018